Dynamics of water waves over fringing reefs - Luk, Max Sau Chiu (2014)
Coral reefs contains a rich mixture of marine organisms and are natural habitat for more than 2 million various species and it mount up to a quarter of percentile of all marine life on Earth (Hearn, C.J., 1999). Example of a coastal region of the Belize Shelf (Jordan, 2002) is shown in Figure 1 for a clearer illustration of the various features of reefs. Coral reefs are commonly found in shallow tropical coastal regions and provide locations where a substantial proportion of surface wave energy is dissipated through wave breaking and bottom friction processes. As such, knowledge of wave processes is an essential part of coral reef hydrodynamics (Yao, 2012).